Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

If x cos a + y sin a = p touches the cuve x^m .y^n = a^(m+n) ;prove that p^(m+n) . m . n = (m+n)^(m+n) cos^m a sin^n a

If x cos a + y sin a = p touches the cuve x^m .y^n = a^(m+n) ;prove that 
     p^(m+n) . m . n = (m+n)^(m+n) cos^m a sin^n a

Grade:12

1 Answers

Nishant Vora IIT Patna
askIITians Faculty 2467 Points
4 years ago
Simplify algebra by making subs X=x/a, Y=y/b and m=n/(n-1)

Xᵐ + Yᵐ = 1 … (i)

Xacotα + Yb = pcosecα … (ii)

Diff (i) wrt X : mXᵐ⁻¹ + mYᵐ⁻¹(dY/dX) = 0 ⟹ dY/dX = −(X/Y)ᵐ⁻¹

At pt of contact (X,Y) have grad (i) = grad (ii) so −acotα/b=−(X/Y)ᵐ⁻¹ … (iii)

Sub in (ii) for acotα : bXᵐ/Yᵐ⁻¹ + Yb = pcosecα ⟹ b(Xᵐ+Yᵐ) = pYᵐ⁻¹cosecα ⟹ Yᵐ⁻¹ = (b/p)sinα

Also using (iii), Xᵐ⁻¹ = (a/p)cosα

Sub in (i) for X,Y and adjust to get (acosα/p)^(m/(m-1)) + (bsinα/p)^(m/(m-1)) = 1

Setting m/(m-1)=n and multiply by pⁿ gives desired result

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free